2013
DOI: 10.1128/aem.02617-12
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Cellulosic Bioethanol Fermentation by Cyclic Fed-Batch Cocultivation

Abstract: f Cocultivation of cellulolytic and saccharolytic microbial populations is a promising strategy to improve bioethanol production from the fermentation of recalcitrant cellulosic materials. Earlier studies have demonstrated the effectiveness of cocultivation in enhancing ethanolic fermentation of cellulose in batch fermentation. To further enhance process efficiency, a semicontinuous cyclic fed-batch fermentor configuration was evaluated for its potential in enhancing the efficiency of cellulose fermentation us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…The cell dry weight–time curve and medium glucose content–time curve were correlated during the cell growth period. Those results were similar to the reports and could be used for the following study (Jiang et al., ; Li et al., ). Z. rouxii was in the lag phase at the initial fermentation stage; thus, the changes in the cell dry weight and glucose content were slow.…”
Section: Resultssupporting
confidence: 89%
“…The cell dry weight–time curve and medium glucose content–time curve were correlated during the cell growth period. Those results were similar to the reports and could be used for the following study (Jiang et al., ; Li et al., ). Z. rouxii was in the lag phase at the initial fermentation stage; thus, the changes in the cell dry weight and glucose content were slow.…”
Section: Resultssupporting
confidence: 89%
“…These data suggests that there is potential to increase the ethanol output from lignocellulosic biomass. Current methods of conversion are affected by cell wall recalcitrance and therefore do not fully liberate the cellulose and hemicellulose from the lignin complex for chemical, microbial or enzymatic depolymerization [25] [26]. Moreover, current methods are not cost-effective to facilitate commercial biomass to ethanol conversion [26] [27].…”
Section: Theoretical Ethanol Yieldmentioning
confidence: 99%
“…It was reported that CBB was anaerobically degraded mainly through fermentation by the genus Clostridium [33]. In fact, the genus Clostridium is widely regarded as important fermentative bacteria [34]. Table 4 clearly showed that the abundance of Clostridium in CBB-amended bulk sediments without SMFC was higher than that with SMFC, which suggested that SMFC might play a role in affecting the microbial metabolism in sediments and inhibit CBB fermentation to some extent.…”
Section: Discussionmentioning
confidence: 96%